Financial reporting demands in a globalised world: The harmonisation of accounting rules - Jan H. Hammermeister; Jochen Zimmermann (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
OECD accounting regimes have significantly changed over the last three decades. Financial reporting rules for (public) companies have become more similar, and the ways in which accounting rules are set and enforced have converged. This paper explores to what extent (financial) globalisation drives convergence of financial reporting systems. We analyse globalisation developments and changes in accounting regulation in six large OECD countries: Canada, France, Germany, Great Britain, Japan and the USA. We identify changes in the demand and supply patters of accounting regulation, and present empirical evidence for the concurrence of financial globalisation and accounting harmonisation. A newly developed financial globalisation index and changes in accounting regulation are jointly analysed. We find that the analysed countries have experienced distinct waves of globalisation since the beginning of the 1970s and that these waves coincide with a delayed accounting harmonisation. – – Die Rechnungslegungssysteme der OECD-Staaten haben sich in den letzten drei Jahrzehnten erheblich verändert. Für kapitalmarktorientierte Unternehmen sind die Rechnungslegungsregeln ähnlicher geworden, und auch die Wege zur Entwicklung und Durchsetzung von Rechnungslegungsnormen haben sich angeglichen. Dieser Beitrag untersucht, in welchem Ausmaß die (finanzielle) Globalisierung eine Konvergenz von Rechnungslegungssystemen vorantreibt. Analysiert werden Globalisierungsentwicklungen und Veränderungen von Rechnungslegungsregulierung in den sechs großen OECD-Staaten: Deutschland, Frankreich, Großbritannien, Japan, Kanada und den USA. Muster im Angebots- und Nachfrageverhalten bezüglich der Regulierung von Rechnungslegung werden untersucht, und dabei wird empirische Evidenz für einen Zusammenfallen von finanzieller Globalisierung und Harmonisierung der Rechnungslegung gefunden. Für die untersuchten Länder können seit Beginn der 1970er Jahre verschiedene Wellen der Globalisierung festgestellt werden, die, zeitlich versetzt, mit einer Harmonisierung von Rechnungslegung korrelieren.
Keywords: 330; Bilanzrecht; Rechtsangleichung; Globalisierung; International Financial Reporting Standards; OECD-Staaten